The importance in diagnosing patients with conflicting observational data for post surgery radioiodinated ablation of thyroid remnants - Simsek, F. S.; Balci, T. A.; Donder, Y.; Ugur, K.; Kilinc, F.; Cetinkaya, Z.; Elmali, F. (Hellenic Soc Nuclear Medicine, 2019)
Objective: There is a special group of patients, according to 2015 American Thyroid Association guidelines. This group is defined as ''the patients with conflicting observational data for post-surgery radioiodine ablation (COD for PSRIA). For this special group of patients RIA is applied after a thorough reassessment of histopathological, clinical and biochemical features, including thyroglobulin (Tg). However, there is no consensus on what is the suitable cut-off value for the radioiodine ablation (RIA) decision or for therapy prediction. Moreover, is also unclear which Tg parameters should be used for these purposes. If we can determine useful and practical cut-off values for excellent response (ER) and non-structural incomplete response (non-SIR) response categories, this will facilitate our therapy response prediction before RIA and may allow us to categorize the group of COD for PSRIA based on a higher risk of recurrence/relapse or disease specific mortality rates according to serum thyroglobulin (Tg). This categorization may also enable us to plan the follow-up frequency of patients more scientifically. Consequently, it may provide the more efficient use of medical facility and healthcare system resources. Subjects and Methods: Two hundred forty-nine patients (out of 577 examined) with COD for PSRIA were included in this study. Firstly, patients with indeterminate, biochemical incomplete and structural incomplete responses were considered as the non-ER group and compared to the ER group. Secondly, patients with excellent, indeterminate, and biochemically incomplete responses were considered as the non-SIR group and compared to the SIR group. The data were evaluated by MedCalc Statistical Software version 18.9. Results: The cut-off value for ER patients was calculated as <= 6.57 ng/mL. Sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) were 67.9%, 75.4%, 55.6% and 83.8%, respectively. The cut-off value for non-SIR patients was calculated as <= 12.7 ng/mL. Sensitivity, specificity, PPV and NPV were 78.5%, 91.7%, 35.5% and 98.6%, respectively. Conclusion: If a patient has <= 6.57ng/mL pre-ablative Tg, follow-up intervals of patients with COD for PSRIA may be extended due to lower recurrence/relapse rates. However, if a patient has >12.7ng/mL pre-ablative Tg, these patients should be followed-up more frequently in order to determine SIR earlier. This approach may enable more efficient use of medical facility and healthcare system resources and a more scientific planning of their follow-up treatment. This approach seems to have the potential to contribute significantly to cost-effectiveness.
Keywords: Thyroid cancer; Thyroglobulin; Predictions for better ablation; I-131 ablation; Conflicting ablation